Alkaline water electrolysis diaphragm based on heterogeneous cortex modification and preparation method thereof
By forming a PA layer and a BILP/GO layer on the alkaline water electrolytic separator, the existing separator is easily damaged and has poor hydrophilicity in high-temperature and concentrated alkali environments, and has achieved higher mechanical strength, airtightness and service life.
Patent Information
- Application Number
- CN202411711907.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-18
AI Technical Summary
The existing alkaline water electrolytic separators are prone to breakage in industrial environments with high temperature concentrated alkali and gas erosion, have poor hydrophilicity, poor gas isolation, and have short service life, so they need to be replaced frequently.
An alkaline water electrolytic separator based on heterocortic layer modification was used to attach the PA layer and the BILP/GO layer in turn to the Zirfon-type base film, and these layers were generated by interfacial polymerization, thereby enhancing the hydrophilicity, mechanical strength and airtightness of the separator.
It achieves excellent hydrophilicity, mechanical strength, airtightness and low surface resistance of the diaphragm, extends its service life, and can be used continuously for more than 6000 hours without performance attenuation under industrial conditions.
Smart Images

Figure CN119640326A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alkaline water electrolysis, and specifically relates to an alkaline water electrolysis diaphragm based on heterogeneous cortex modification and a preparation method thereof. Background Art
[0002] Green hydrogen is hydrogen produced by combining renewable energy power systems with water electrolysis technology. It is a perfect solution to achieve zero carbon emissions. Water electrolysis hydrogen production technology with membrane materials as key components is a key link and the best way to produce low-cost green hydrogen. Usually, an alkaline water electrolysis device includes an electrolyzer, electrodes and a diaphragm. When powered on, hydrogen is produced on the cathode side and oxygen is produced on the anode side.
[0003] The diaphragm is the core component of the alkaline electrolyzer, and its main function is to separate the positive and negative electrodes and to block the gas. The porous diaphragm is mainly composed of porous inactive materials. Since it does not have electrical conductivity, it mainly relies on the electrolyte filled in the gaps of the material itself to achieve ion conduction. The composite diaphragm of the electrolyzer is an organic-inorganic hybrid composite diaphragm obtained by hybridizing and weaving organic heat-resistant and alkali-resistant polymers with hydrophilic inorganic non-metallic oxides in different ways. In the process of industrial operation, the current commercial diaphragms cannot quickly infiltrate the electrolyte due to insufficient hydrophilicity. They are easily damaged in the industrial operation environment of high temperature, concentrated alkali, and gas scouring. The internal pore size of the diaphragm is too large, resulting in poor gas barrier properties, and it cannot be used for a long time and needs to be replaced frequently. Therefore, the diaphragm is generally required to have good hydrophilicity, mechanical properties, gas barrier properties, and chemical stability.
[0004] The first generation of asbestos diaphragms have long been used as the main raw material for water electrolyzer diaphragms, but due to their high resistance, poor stability and toxicity, their application is strictly restricted, and new non-asbestos diaphragms have become one of the research directions; the current existing diaphragms include polyphenylene sulfide (PPS) woven cloth diaphragms, but their high energy consumption and low current density limit their application; Zirfon-type base membranes have excellent alkali stability and are regarded as the preferred material for alkaline electrolysis water diaphragms, but this polymer membrane has poor hydrophilicity and easily leads to bubble adhesion, which not only increases the solution resistance and reduces the electrolysis efficiency, but also has a large internal pore size of the diaphragm, which is prone to gas cross-over, thereby causing explosions; AGFA's Zirfon series diaphragms have low energy consumption and high current density and have attracted widespread attention, but they are expensive, the internal pore size of the diaphragm is large, so the gas barrier is poor, and the diaphragm lacks effective means to strengthen mechanical properties, so the tensile and puncture resistance are poor.
[0005] Therefore, there is an urgent need to provide a diaphragm for producing hydrogen by alkaline water electrolysis with excellent performance and low cost. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an alkaline water electrolysis diaphragm based on heterogeneous cortex modification and a preparation method thereof, so as to prepare an alkaline water electrolysis diaphragm having excellent hydrophilicity, mechanical strength, air tightness and surface resistance.
[0007] The present invention solves the technical problem by the following technical solutions:
[0008] An alkaline water electrolysis diaphragm based on heterogeneous cortex modification, the alkaline water electrolysis diaphragm consists of a Zirfon-type base membrane, a PA layer and a BILP / GO layer, the PA layer and the BILP / GO layer are sequentially attached to the Zirfon-type base membrane, and the PA layer and the BILP / GO layer are both generated by interfacial polymerization reaction.
[0009] Moreover, the thickness of the alkaline water electrolysis membrane is 100-500 μm, the thickness of the PA layer is 50-150 nm, and the thickness of the BILP / GO layer is 100-400 nm.
[0010] Moreover, the alkaline water electrolysis membrane has a contact angle of 50°, a maximum tensile load of 28 MPa, a maximum puncture force of 213 N, a bubble point pressure of 11.3 bar, and a surface resistance of 0.24 Ω·cm 2 , the continuous use time without performance degradation exceeds 6000 hours.
[0011] A method for preparing an alkaline water electrolysis diaphragm based on heterogeneous cortex modification, wherein the alkaline water electrolysis diaphragm is prepared, and the steps of the method are as follows:
[0012] S1, preparation of additive GO;
[0013] S2, Zirfon type basement membrane surface pretreatment;
[0014] S3, dissolving inorganic monomers piperazine and 1,2,4,5-benzenetetramine tetrahydrochloride in water to prepare a PA layer aqueous phase solution and a BILP layer aqueous phase solution, and adding an additive GO to the BILP layer aqueous phase solution;
[0015] S4, organic phase monomers trimesoyl chloride and 1,3,5-benzenetricarbaldehyde are dissolved in organic solvents n-hexane and 1,2-dichloroethane respectively to prepare a PA layer organic phase solution and a BILP layer organic phase solution;
[0016] S5, soaking the pretreated Zirfon type base membrane in the PA layer aqueous phase solution and the PA layer organic phase solution in turn to perform interfacial polymerization reaction, so as to obtain a Zirfon type base membrane with a PA layer attached to the surface;
[0017] S6. Soaking the Zirfon-type base film with the PA layer attached to the surface in the BILP layer aqueous solution and the BILP layer organic solution in turn to perform interfacial polymerization reaction, thereby obtaining the alkaline water electrolysis membrane.
[0018] Moreover, the content of the additive GO is 0.1-0.4 wt%.
[0019] Moreover, S5 specifically comprises soaking the Zirfon-type base membrane in an aqueous solution of piperazine and an n-hexane solution of trimesoyl chloride for a certain period of time, and forming a PA layer on the outer surface of the Zirfon-type base membrane after the diaphragm is naturally dried; S6 specifically comprises soaking the Zirfon-type base membrane with a PA layer in a mixed aqueous solution of 1,2,4,5-benzenetetramine tetrahydrochloride and GO and a 1,2-dichloroethane solution of 1,3,5-benzenetricarboxaldehyde, and forming an alkali-resistant and high-temperature-resistant BILP / GO layer on the PA layer again after the diaphragm is naturally dried.
[0020] The advantages and beneficial effects of the present invention are:
[0021] 1. The present invention can improve the hydrophilicity of the alkaline water electrolysis membrane. The BILP layer on the outer surface of the alkaline water electrolysis membrane contains GO, whose rich oxygen-containing functional groups can form hydrogen bonds with water molecules, greatly improving the adsorption capacity of water molecules, allowing water molecules to quickly aggregate and penetrate into the cortex, thereby promoting ion permeation through the membrane;
[0022] 2. The preparation method of the present invention not only has little effect on the thickness of the diaphragm itself, but also can maintain the original permeability, porosity and other characteristics of the diaphragm. Therefore, there is no problem of increasing the surface resistance of the diaphragm due to the excessive thickness of the skin layer. At the same time, the dense microporous structure of the strengthened skin layer can provide strong mechanical properties and gas barrier capabilities. This is due to the combined effect of the highly elastic and impact-resistant PA layer and the dense and chemically stable BILP layer, which is conducive to taking into account both the gas barrier and mechanical properties of the composite diaphragm.
[0023] 3. The heterogeneous reinforced skin structure adopted in the present invention has better gas barrier performance, the high-strength and high-elasticity PA layer improves the mechanical strength, the chemically stable BILP layer improves the high-temperature alkali resistance of the diaphragm, and the large number of oxygen-containing functional groups on the additive GO brings higher hydrophilicity and lower surface resistance, so that the reinforced alkaline water electrolysis diaphragm can operate better for a long time without damage in the harsh environment of industrial hydrogen production.
[0024] 4. The present invention forms a dense and ultra-thin PA layer on the outer surface of the Zirfon type base membrane by immersing the Zirfon type base membrane in an inorganic phase with piperazine as solute and water as solvent and in an organic phase with trimesoyl chloride as solute and n-hexane as solvent for a certain period of time.
[0025] 5. The present invention uniformly disperses GO of a specific concentration in an inorganic phase with 1,2,4,5-benzenetetramine tetrahydrochloride as a solute and water as a solvent. With the help of GO's abundant oxygen-containing functional groups, GO can be quickly and uniformly dispersed in the inorganic phase.
[0026] 6. The present invention forms a more alkali-resistant and heat-resistant BILP / GO layer on the outer surface by immersing the Zirfon-type base film with a PA layer in an inorganic phase and an organic phase with 1,3,5-benzenetricarboxaldehyde as a solute and 1,2-dichloroethane as a solvent for a certain period of time.
[0027] 7. The contact angle of the alkaline water electrolysis diaphragm prepared by the present invention decreases from 105° to 50°, the maximum tensile load increases from 16MPa to 28MPa, the maximum puncture force increases from 153N to 213N, the bubble point pressure increases from 5.2bar to 11.3bar, and the surface resistance increases from 0.85Ω·cm 2 Down to 0.24Ω·cm 2 , when using commercial catalysts and under industrial conditions, it can be used continuously for more than 6000 hours without performance degradation. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a preparation flow chart of the present invention;
[0029] Figure 2 This is a schematic diagram of the structure of the alkaline water electrolysis diaphragm prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0031] In the first aspect, the present invention provides an alkaline water electrolysis diaphragm based on heterogeneous cortical modification, wherein the alkaline water electrolysis diaphragm can be any alkaline water electrolysis diaphragm used in industrialization, for example, a Zirfon-type base membrane with a PPS mesh as a support, ceramic hydrophilic particles and high molecular organic polymers, and the diaphragm obtained by the present invention is composed of a Zirfon-type base membrane, and a PA layer and a BILP / GO layer formed on the outer surface of the Zirfon-type base membrane. The PA layer and the BILP / GO layer are both generated by interfacial polymerization, and an additive GO that can effectively improve the performance of the diaphragm is added during the interfacial polymerization.
[0032] The alkaline water electrolyzer diaphragm is a key component in alkaline water electrolysis, which is used to separate the anode and cathode and prevent the mixing of hydrogen and oxygen. At present, the industry generally coats a slurry including inorganic nanoparticles, organic high molecular polymers and binders on the surface of a support such as polypropylene and polyethylene to obtain a diaphragm for alkaline water electrolysis. However, the above-mentioned diaphragm has poor hydrophilicity and is prone to cause bubble adhesion, which not only increases the solution resistance and reduces the electrolysis efficiency, but also aggravates gas crossover and easily causes explosion hazards; the internal pore size of the diaphragm is large, so the gas barrier is poor; the diaphragm lacks effective mechanical property strengthening means, so the tensile resistance and puncture resistance are poor.
[0033] The present invention adopts a heterogeneous cortical structure design of PA layer and BILP / GO layer, which can not only obtain an alkaline water electrolysis diaphragm with ultra-high bubble point pressure, but also the diaphragm has extremely low surface resistance, extremely high hydrophilicity, extremely strong mechanical properties and extremely high stability.
[0034] The PA layer generated by the skin strengthening measures adopted in the present invention can be regarded as a dense, ultra-thin nylon skin layer, which has dense nanopores, can quickly absorb and infiltrate electrolyte, and provides ultra-high tensile and puncture resistance. The BILP layer is a type of porous organic framework known to have high thermal and chemical stability and high microporosity. When the neutral benzimidazole group in the BILP layer is attacked by hydroxide ions at the C2 position, it will cause the ring to crack and generate carbonyl C-O and amide bonds, and then the amide is hydrolyzed. Under alkaline conditions, the benzimidazole group is deprotonated to become a benzimidazole anion, and nucleophilic addition occurs at the C2 position to generate an alkoxy anion. The benzimidazole anions, carboxylates and alkoxy anions generated by the degradation of BILP can prevent hydroxide ions from further entering and attacking BILP, making the BILP layer extremely stable in a strong alkaline environment. GO, which is added to the BILP layer as an additive, brings extremely high hydrophilicity to the BILP / GO layer due to its rich oxygen-containing functional groups and superior stability.
[0035] The present invention has been verified by a large number of experiments, and the thickness variation of the composite membrane is controlled within the nanometer scale. The thickness of the obtained composite membrane is very thin and meets various performance requirements.
[0036] According to some embodiments of the present invention, the concentration of GO is 0.1wt% to 0.4wt%. GO is a nanosheet with multiple oxygen-containing groups and aromatic groups. Its oxygen-containing groups act as OH - The migration sites of ions allow anions to migrate quickly in the diaphragm; the oxygen-containing groups form hydrogen bonds with water molecules, providing higher hydrophilicity.
[0037] According to some embodiments of the present invention, the interfacial polymerization technology refers to two highly reactive monomers dissolved in two immiscible solvents, respectively, and an irreversible polycondensation reaction is carried out at the interface of the two phases. Through the interfacial polymerization reaction, a better material is modified on the original industrial water electrolysis membrane in a safer, more stable and efficient manner. On the one hand, the dense interfacial polymerization layer has excellent thermochemical stability and high water flux, so as to improve the durability of the membrane and promote OH - Ion conduction; on the other hand, interfacial polymerization can firmly attach the modified material to the original membrane for a long time and retain the performance of the original membrane.
[0038] In a second aspect, the present invention provides a method for preparing an alkaline water electrolysis diaphragm based on heterogeneous cortex modification, such as Figure 1 shown.
[0039] Example 1
[0040] This embodiment provides a method for preparing an alkaline water electrolysis diaphragm based on heterogeneous cortex modification, such as Figure 2 As shown, the prepared diaphragm is composed of a Zirfon-type base membrane and a PA layer and a BILP / GO layer formed on the outer surface of the Zirfon-type base membrane. The preparation method comprises the following steps:
[0041] Step 1: Place graphite powder in a beaker, add concentrated sulfuric acid and phosphoric acid and stir, add KMnO4 in an ice water bath and continue stirring for 15 minutes.
[0042] Step 2: Place the beaker in a constant temperature water bath at 30-45°C and control the stirring time of the medium temperature water bath to 2 hours.
[0043] Step 3: After the medium temperature reaction, add distilled water to the mixed solution, transfer it to a constant temperature water bath at 85-95°C for stirring, take it out after 15 minutes and add another 50mL of distilled water. After the high temperature reaction, add 2mL of hydrogen peroxide.
[0044] Step 4: wash the mixed solution with distilled water until it is neutral and perform 40kHz ultrasound for 1 hour, centrifuge the mixed solution, take the supernatant and dry it at 95°C for 24 hours to obtain dry GO.
[0045] Step 5, the Zirfon type basement membrane is soaked in ethanol and deionized water for 30 minutes respectively to remove impurities on the surface of the Zirfon type basement membrane;
[0046] Piperazine is dissolved in water to prepare a uniform aqueous phase solution with a concentration of 0.5 wt %. Trimesoyl chloride is dissolved in n-hexane to prepare an organic phase solution with a concentration of 0.5 wt %;
[0047] Subsequently, the pretreated Zirfon-type base membrane was completely immersed in the aqueous solution, taken out after 60 seconds, and placed in a cool place to drain the residual water on the surface of the membrane.
[0048] Step 6: After the Zirfon-type base film is dried, it is immersed in an organic phase for 60 seconds to allow piperazine and trimesoyl chloride to undergo interfacial polymerization on the surface of the Zirfon-type base film to form a PA layer. Finally, the film is moved to a 70°C electric constant temperature drying oven for heat treatment and taken out after 20 minutes for use.
[0049] Step 7, 1,2,4,5-benzenetetramine tetrahydrochloride is dissolved in water to prepare an aqueous solution with a concentration of 0.1wt%, and then GO is dissolved in the aqueous solution to prepare an aqueous solution with a mass ratio of 1,2,4,5-benzenetetramine tetrahydrochloride to GO of 1:1, and ultrasonicated for 1h to make the solution evenly distributed. 1,3,5-benzenetricarboxaldehyde is dissolved in 1,2-dichloroethane to prepare an organic phase solution with a concentration of 0.1wt%. Subsequently, the Zirfon-type base membrane with the attached PA layer is completely immersed in the aqueous solution, taken out after 60s, and placed in a cool place to drain the residual moisture on the surface of the membrane.
[0050] Step 8: After the Zirfon-type base film is dried, it is immersed in an organic phase for 60 seconds to allow 1,2,4,5-benzenetetramine tetrahydrochloride and 1,3,5-benzenetricarbox to undergo interfacial polymerization reaction on the surface of the film to form a BILP / GO layer. Finally, the film is moved to a 70°C electric constant temperature drying oven for heat treatment and taken out after 20 minutes to obtain a diaphragm.
[0051] Example 2
[0052] This embodiment provides a method for preparing an alkaline water electrolysis diaphragm based on heterogeneous cortex modification. The prepared diaphragm is composed of a Zirfon-type base membrane and a BILP / GO layer formed on the outer surface of the Zirfon-type base membrane. The preparation method comprises the following steps:
[0053] Step 1: Place graphite powder in a beaker, add concentrated sulfuric acid and phosphoric acid and stir, add KMnO4 in an ice water bath and continue stirring for 15 minutes.
[0054] Step 2: Place the beaker in a constant temperature water bath at 30-45°C and control the stirring time of the medium temperature water bath to 2 hours.
[0055] Step 3: After the medium temperature reaction, add distilled water to the mixed solution, transfer it to a constant temperature water bath at 85-95°C for stirring, take it out after 15 minutes and add another 50mL of distilled water. After the high temperature reaction, add 2mL of hydrogen peroxide.
[0056] Step 4: wash the mixed solution with distilled water until it is neutral and perform 40kHz ultrasound for 1 hour, centrifuge the mixed solution, take the supernatant and dry it at 95°C for 24 hours to obtain a dry GO sample.
[0057] Step 5: 1,2,4,5-benzenetetramine tetrahydrochloride is dissolved in water to prepare an aqueous solution with a concentration of 0.1wt%, and then GO is dissolved in the aqueous solution to prepare an aqueous solution with a mass ratio of 1,2,4,5-benzenetetramine tetrahydrochloride to GO of 1:1, and the solution is evenly distributed by ultrasound for 1h. 1,3,5-benzenetricarboxaldehyde is dissolved in 1,2-dichloroethane to prepare an organic phase solution with a concentration of 0.1wt%. Subsequently, the Zirfon-type base membrane with the attached PA layer is completely immersed in the aqueous solution, taken out after 60s, and placed in a cool place to drain the residual moisture on the surface of the membrane.
[0058] Step 6: After the Zirfon-type base film is dried, it is immersed in an organic phase for 60 seconds to allow 1,2,4,5-benzenetetramine tetrahydrochloride and 1,3,5-benzenetricarbox to undergo interfacial polymerization on the surface of the film to form a BILP / GO layer. Finally, the film is moved to a 70°C electric constant temperature drying oven for heat treatment and taken out after 20 minutes to obtain a diaphragm.
[0059] Example 3
[0060] This embodiment provides a method for preparing an alkaline water electrolysis diaphragm based on heterogeneous cortex modification. The prepared diaphragm is composed of a Zirfon-type base membrane and a PA / GO layer formed on the outer surface of the Zirfon-type base membrane. The preparation method comprises the following steps:
[0061] Step 1: Place graphite powder in a beaker, add concentrated sulfuric acid and phosphoric acid and stir, add KMnO4 in an ice water bath and continue stirring for 15 minutes.
[0062] Step 2: Place the beaker in a constant temperature water bath at 30-45°C and control the stirring time of the medium temperature water bath to 2 hours.
[0063] Step 3: After the medium temperature reaction, add distilled water to the mixed solution, transfer it to a constant temperature water bath at 85-95°C for stirring, take it out after 15 minutes and add another 50mL of distilled water. After the high temperature reaction, add 2mL of hydrogen peroxide.
[0064] Step 4: wash the mixed solution with distilled water until it is neutral and perform 40kHz ultrasound for 1 hour, centrifuge the mixed solution, take the supernatant and dry it at 95°C for 24 hours to obtain a dry GO sample.
[0065] Step 5, the Zirfon-type base membrane is first soaked in ethanol and deionized water for 30 minutes each to remove impurities on the surface of the Zirfon-type base membrane. Piperazine is dissolved in water to prepare a uniform aqueous solution with a concentration of 0.5wt%, and then GO is dissolved in the aqueous solution to prepare an aqueous solution with a mass ratio of piperazine to GO of 1:1, and ultrasonicated for 1h to make the solution uniformly distributed. Triphenylmethane dichloride is dissolved in n-hexane to prepare an organic phase solution with a concentration of 0.5wt%. Subsequently, the pretreated Zirfon-type base membrane is completely immersed in the aqueous solution, taken out after 60s, and placed in a cool place to drain the residual moisture on the surface of the membrane.
[0066] Step 6: After the Zirfon-type base film is dried, it is immersed in an organic phase for 60 seconds to allow piperazine and trimesoyl chloride to undergo interfacial polymerization on the surface of the Zirfon-type base film to form a PA / GO layer. Finally, the film is moved to a 70°C electric constant temperature drying oven for heat treatment and taken out after 20 minutes to obtain a separator.
[0067] Example 4
[0068] This embodiment provides a method for preparing an alkaline water electrolysis diaphragm based on heterogeneous cortex modification. The prepared diaphragm is composed of a Zirfon-type basement membrane and a PA layer and a BILP layer formed on the outer surface of the Zirfon-type basement membrane. The preparation method comprises the following steps:
[0069] Step 1: The Zirfon-type basement membrane is first soaked in ethanol and deionized water for 30 minutes each to remove impurities on the surface of the Zirfon-type basement membrane. Piperazine is dissolved in water to prepare a uniform aqueous phase solution with a concentration of 0.5wt%. Tris(oyl)chloride is dissolved in n-hexane to prepare an organic phase solution with a concentration of 0.5wt%. Subsequently, the pretreated Zirfon-type basement membrane is completely immersed in the aqueous phase solution, taken out after 60 seconds, and placed in a cool place to drain the residual moisture on the surface of the membrane.
[0070] Step 2: After the Zirfon-type base film is dried, it is immersed in an organic phase for 60 seconds to allow piperazine and trimesoyl chloride to undergo an interfacial polymerization reaction on the surface of the Zirfon-type base film to form a PA layer. Finally, the film is moved to a 70°C electric constant temperature drying oven for heat treatment and taken out after 20 minutes for use.
[0071] Step 3: 1,2,4,5-benzenetetramine tetrahydrochloride is dissolved in water to prepare a 0.1wt% aqueous solution. 1,3,5-benzenetricarboxaldehyde is dissolved in 1,2-dichloroethane to prepare a 0.1wt% organic solution. Subsequently, the Zirfon-type base film with the PA layer attached is completely immersed in the aqueous solution, taken out after 60s, and placed in a cool place to drain the residual water on the surface of the film.
[0072] After the Zirfon-type base film is dried, it is immersed in an organic phase for 60 seconds to allow 1,2,4,5-benzenetetramine tetrahydrochloride and 1,3,5-benzenetricarbox to undergo interfacial polymerization on the surface of the film to form a BILP layer. Finally, the film is moved to a 70°C electric constant temperature drying oven for heat treatment and taken out after 20 minutes to obtain a diaphragm.
[0073] Comparative Example 1
[0074] This comparative example provides a composite diaphragm for alkaline water electrolysis, which is ZIRFON PERL UTP500, purchased from Agfa-Gevaert.
[0075] Comparative Example 2
[0076] This comparative example provides a composite diaphragm for alkaline water electrolysis, and its preparation method is as follows:
[0077] Step 1: The Zirfon-type basement membrane is first soaked in ethanol and deionized water for 30 minutes each to remove impurities on the surface of the Zirfon-type basement membrane. Subsequently, the pretreated Zirfon-type basement membrane is completely immersed in water, taken out after 60 seconds, and placed in a cool place to drain the residual water on the membrane surface.
[0078] Step 2: After the Zirfon-type base film is dried, it is immersed in n-hexane for 60 seconds, and then the film is moved to a 70° C. electric constant temperature drying oven for heat treatment, and taken out after 20 minutes for use.
[0079] Step 3: completely immerse the treated Zirfon-type base film in water, take it out after 60 seconds, and place it in a cool place to drain the residual water on the surface of the film.
[0080] Step 4: After the Zirfon-type base film is dried, it is immersed in 1,2-dichloroethane for 60 seconds, and then the film is moved to a 70°C electric constant temperature drying oven for heat treatment, and taken out after 20 minutes for use.
[0081] Performance Testing
[0082] The performance tests were conducted on the diaphragms of Examples 1 to 4 of the present invention and Comparative Examples 1 and 2. The results are shown in Table 1.
[0083] The test method of the surface resistance is as follows: the diaphragm is cut into small pieces, and after being immersed in a 30 wt % KOH solution for 1 day, the resistance is tested using an electrochemical workstation.
[0084] The test method of bubble point pressure is as follows:
[0085] Cut the membrane into small pieces, soak them with high-purity water, and put them into the bubble pressure membrane pore size analyzer (BSD-PB) for testing. Apply gas pressure on one side of the membrane. When a gas flow of 1 mL / min is detected on the other side of the membrane, the pressure is regarded as the bubble point pressure of the membrane. The calculation formula of the bubble point is as follows:
[0086] P bubble =RT(1+VB) / V, where: P bubble is the bubble point pressure (Pascals). R is the ideal gas constant (8.314 J / (mol·K)). T is the absolute temperature (Kelvin). V is the molar volume of the gas (cubic meters / mole). B is the Birch constant in the Birch-Murnaghan equation.
[0087] The maximum puncture force and the maximum tensile load are tested using conventional testing methods in the art.
[0088] The test method for hydrophilicity is as follows:
[0089] The separator was cut into small pieces and immersed in a 30 wt % KOH solution for 1 day, and then the contact angle of the separator was measured using a contact angle meter.
[0090] The stability test method is as follows:
[0091] The membrane was cut into small pieces and immersed in a 30 wt% KOH solution for 20 days. 2 Under the conditions of , the tank pressure before and after immersion was measured, and the percentage of tank pressure decrease was calculated.
[0092] Table 1 Performance test table
[0093]
[0094] As shown in Table 1, the contact angle of the alkaline water electrolysis diaphragm prepared by the present invention decreases from 105° to 50°, the maximum tensile load increases from 16MPa to 28MPa, the maximum puncture force increases from 153N to 213N, the bubble point pressure increases from 5.2bar to 11.3bar, and the surface resistance increases from 0.85Ω·cm 2 Down to 0.24Ω·cm 2 .
[0095] Although the embodiments and drawings of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments and drawings.
Claims
1. An alkaline water electrolysis diaphragm based on heterogeneous cortex modification, characterized in that: The alkaline water electrolysis membrane consists of a Zirfon-type base membrane, a PA layer and a BILP / GO layer. The PA layer and the BILP / GO layer are sequentially attached to the Zirfon-type base membrane. The PA layer and the BILP / GO layer are both generated by interfacial polymerization reaction.
2. The alkaline water electrolysis diaphragm based on heterogeneous cortex modification according to claim 1, characterized in that: The thickness of the alkaline water electrolysis membrane is 100-500 μm, the thickness of the PA layer is 50-150 nm, and the thickness of the BILP / GO layer is 100-400 nm.
3. The alkaline water electrolysis diaphragm based on heterogeneous cortex modification according to claim 1, characterized in that: The alkaline water electrolysis membrane has a contact angle of 50°, a maximum tensile load of 28 MPa, a maximum puncture force of 213 N, a bubble point pressure of 11.3 bar, and a surface resistance of 0.24 Ω·cm 2 , the continuous use time without performance degradation exceeds 6000 hours.
4. A method for preparing an alkaline water electrolysis diaphragm based on heterogeneous cortex modification, characterized in that: Preparation of the alkaline water electrolysis membrane according to any one of claims 1 to 4, the method comprising the steps of: S1, preparation of additive GO; S2, Zirfon type base film surface pretreatment; S3, dissolving inorganic monomers piperazine and 1,2,4,5-benzenetetramine tetrahydrochloride in water to prepare a PA layer aqueous phase solution and a BILP layer aqueous phase solution, and adding an additive GO to the BILP layer aqueous phase solution; S4, organic phase monomers trimesoyl chloride and 1,3,5-benzenetricarbaldehyde are dissolved in organic solvents n-hexane and 1,2-dichloroethane respectively to prepare a PA layer organic phase solution and a BILP layer organic phase solution; S5, soaking the pretreated Zirfon type base membrane in the PA layer aqueous phase solution and the PA layer organic phase solution in turn to perform interfacial polymerization reaction, so as to obtain a Zirfon type base membrane with a PA layer attached to the surface; S6. Soaking the Zirfon-type base film with the PA layer attached to the surface in the BILP layer aqueous solution and the BILP layer organic solution in turn to perform interfacial polymerization reaction, thereby obtaining the alkaline water electrolysis membrane.
5. The method for preparing an alkaline water electrolysis diaphragm based on heterogeneous cortex modification according to claim 5, characterized in that: The content of the additive GO is 0.1-0.4 wt%. The method for preparing an alkaline water electrolysis diaphragm based on heterogeneous cortex modification according to claim 5 is characterized in that: The S5 specifically comprises soaking the Zirfon-type base membrane in an aqueous solution of piperazine and an n-hexane solution of trimesoyl chloride for a certain period of time, and forming a PA layer on the outer surface of the Zirfon-type base membrane after the diaphragm is naturally dried; the S6 specifically comprises soaking the Zirfon-type base membrane with a PA layer in a mixed aqueous solution of 1,2,4,5-benzenetetramine tetrahydrochloride and GO and a 1,2-dichloroethane solution of 1,3,5-benzenetricarboxaldehyde, and forming an alkali-resistant and high-temperature-resistant BILP / GO layer on the PA layer again after the diaphragm is naturally dried.